(untitled) (Bangladesh Journal of Medical Science, 2024)
Aim Polycythemia, also known as erythrocytosis, is an abnormal accumulation of red blood cells, packed cell volume, and hemoglobin that can lead to debilitating symptoms and significant mortality. Polycythemia is estimated to affect 22 people per 100,000. The epidemiology of polycythemia in Iraq is limited. This study aimed to investigate the prevalence and incidence of polycythemia in Babylon City, Iraq, from 2018 to 2022 and to identify populations at high risk. Materials and Methods Due to the relative scarcity of epidemiological studies on polycythemia in Iraq, this study was conducted to identify some epidemiological features of polycythemia patients in Babylon province. A study conducted at the Babylon Central Blood Bank included 220 polycythemia patients. This data was obtained by reviewing all patient documents and the registration book from 2018 to 2022. Participants completed a questionnaire with information about their Sex, age, place of residence, smoking habits, and blood group. Statistics were analyzed using SPSS version 23.0 and Prism software. Results were presented in numbers and percentages and analyzed using the Chi-square test. Results Results indicated that polycythemia increased between 2018 and 2020, with the highest numbers in 2018 and decreasing in 2022. There was a higher frequency in the age group of (41-50) years, and it was more common in males with polycythemia (92.72%) who were smokers (79.09%). Most polycythemia patients had the B blood group (38.2%), while the AB blood group had the lowest percentage (5.5%), and most cases were Rh-positive (91.8%). Conclusion this study provided an overview of the epidemiology of polycythemia in Babylon, Iraq. The findings indicate that polycythemia was more prevalent in men of middle age and with blood group B+. Therefore, further research is needed to examine the relevance of the ABO blood group to polycythemia severity and susceptibility. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1068-1074